The effect of lavender aromatherapy and deep breathing exercise on anxietas level in hemodialysis patients - Retnaningsih, Dwi; Jumiati, Jumiati; Prihati, Dyah Restuning (International Journal of Public Health Science (IJPHS), 2024)
Chronic kidney failure is a chronic disease that requires treatment and hemodialysis therapy. Hemodialysis therapy has physical and psychological impacts on patients, such as stress. Patients who experience stress require management techniques such as lavender aromatherapy and deep breathing relaxation. The purpose of the study was to compare the effects of lavender aromatherapy and deep breathing relaxation on patients receiving hemodialysis who were experiencing the stress of chronic kidney failure. The study's quasi-experimental design includes two groups for the pretest and posttest. The 32 patients with chronic renal failure receiving hemodialysis made up the research sample; 16 of them participated in the lavender aromatherapy intervention and 16 were part of the deep breathing relaxation group. The research instrument used is the perceived stress scale (PSS) questionnaire. With a p-value of 0.000, data analysis employing an independent t-test reveals a difference between the deep breathing relaxation and lavender aromatherapy interventions on the stress of chronic renal failure patients receiving hemodialysis. Lavender aromatherapy and breathing relaxation can reduce stress in chronic kidney failure patients undergoing hemodialysis. Lavender aromatherapy reduces stress in chronic kidney failure patients more effectively than deep breathing relaxation. Lavender aromatherapy can be an alternative therapy to reduce stress while undergoing hemodialysis.